2017
DOI: 10.1021/acsnano.7b04888
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Immiscibility at the Edge of the Nanoscale

Abstract: In the quest to identify more effective catalyst nanoparticles for many industrially important applications, the Au-Pt system has gathered considerable attention. Despite considerable effort the interplay between phase equilibrium behavior and surface segregation in Au-Pt nanoparticles is still poorly understood. Here we investigate the phase equilibrium behavior of 20 nm Au-Pt nanoparticles using a combination of high-resolution scanning transmission electron microscopy and a hybrid Monte Carlo and molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…[88][89][90]91,92 Scanning tunneling microscopy of Pt evaporated on Au (111) shows that Pt embeds in the surface layer at ϑ < 0.03, and forms alloyed islands above this coverage with the Pt concentration of the islands increasing to 50% by the point of island coalescence. 91 Immiscibility and phase segregation in Au@Pt NCs have been observed by TEM, where, upon annealing, Pt segregates under a monolayer of Au, 93,94 consistent with theoretical predictions. 95,96 The same picture is further supported by the observed core level shifts shown in Figure 1F.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…[88][89][90]91,92 Scanning tunneling microscopy of Pt evaporated on Au (111) shows that Pt embeds in the surface layer at ϑ < 0.03, and forms alloyed islands above this coverage with the Pt concentration of the islands increasing to 50% by the point of island coalescence. 91 Immiscibility and phase segregation in Au@Pt NCs have been observed by TEM, where, upon annealing, Pt segregates under a monolayer of Au, 93,94 consistent with theoretical predictions. 95,96 The same picture is further supported by the observed core level shifts shown in Figure 1F.…”
Section: Resultssupporting
confidence: 76%
“…At low coverage, Pt is known to form 2D islands on Au, with Pt embedded in the surface and subsurface layer to form a bimetallic interface. Scanning tunneling microscopy of Pt evaporated on Au(111) shows that Pt embeds in the surface layer at ϑ < 0.03 and forms alloyed islands above this coverage with the Pt concentration of the islands increasing to 50% by the point of island coalescence . Immiscibility and phase segregation in Au@Pt NCs have been observed by TEM, where, upon annealing, Pt segregates under a monolayer of Au, , consistent with theoretical predictions. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Comprehensive sampling also allows us to discover ground-state chemical configurations that are more revealing than previously reported. For segregating systems, computational studies have generally found that the energetically most favorable particle has a core–shell structure, possibly with the core positioned off-center. ,, Here, we show that while this is often the case, the notion of a core surrounded by a shell is to some extent misleading, since the shape of the segregate is largely governed by the structural motif and may at some compositions attain highly symmetric, e.g., ring-like, configurations that cannot be described as core–shell.…”
Section: Introductionmentioning
confidence: 75%
“…From a practical standpoint, these are, however, just as important as particles experimentally are almost always found off-equilibrium, in local minima that are bound by very substantial energy barriers . This realization has motivated a multitude of studies with different approaches, including genetic algorithms and basin hopping , as well as molecular dynamics (MD) and Monte Carlo (MC) simulations. , …”
Section: Introductionmentioning
confidence: 99%
“…For example, the migration of core Au atoms to the thin layer of Pt surfaces was observed in spherical Au NPs 13 or rod shape Au NPs. 14 The gradual change of Au@Pt core-shell structure to the phase-separated Au-Pt NPs was also identified at 403 °C, 15 or over 600 °C. 16 Nonetheless, whether it is due to its inertness with moisture and air, or its reluctance to the oxidation, Au cores undergo little structural changes, as many experiments show seemingly stable Au cores with Pt shells.…”
Section: Introductionmentioning
confidence: 92%